Visual Basic 2005 by practice - Mostafavi, Mike. (Boston : Charles River Media, 2006)
Provides students with an understanding of the language by teaching concepts through step-by-step and concise examples. This book covers important topics such as interactive programming, database features, debugging, and Web controls. It also accompanies a CD-ROM, which allows students to see the programs in action and examine their features.
Includes index.
Keywords: Visual Basic; Visual Basic (Computer program language).; Microsoft Visual BASIC